Utilizing chitosan and titanium dioxide nanomaterials and their nanocomposites for improving the growth and biochemical responses of Sorghum bicolor (L.) - Rani, Neelam; Kumari, Kusum; Hooda, Vinita (Plant Science Today, 2024)
It is imperative to comprehensively assess the impact of nano-based technologies on plants and ensure their safety before integrating them into agricultural practices. In this context, the present study demonstrates the effect of nanosized chitosan (CS), titanium dioxide (TiO2), and CS/TiO2 nanocomposites (NCPs) on Sorghum bicolor (L.) Moench, the fifth most important grain crop globally. The nanomaterials were chemically synthesized and characterized in terms of size, surface morphology, structure, functional groups, and hydrodynamic diameter. S. bicolor plants were cultivated in soil spiked with these nanomaterials at two different concentrations (100 and 200 ppm) for up to 30 days. Compared to control plants, all three nanomaterials stimulated the growth of S. bicolor by 3-23% and enhancednutrient uptake. Additionally, they increased the concentrations of chlorophyll (35-94%), starch (13-19%), cellulose (12-56%), and protein (3-119%) in the shoots, while reducing the malondialdehyde (MDA) content. However, elevated MDA levels in the roots of plants treated with TiO2 nanoparticles and CS/TiO2 NCPs indicated that mild oxidative stress had occurred, which the plant managed to counteract by enhancing antioxidant enzyme activities. The findings of this study confirm the safety of using these nanomaterials and provide a foundation for future research aimed at enhancing the growth, adaptability, and yield of S. bicolor.